PENINGKATAN MINAT BACA SISWA MELALUI PENGEMBANGAN PERPUSTAKAAN BERBASIS DIGITAL - Asadi, Ahmad Ahya; Dharmayanti, Agustin Wulan Suci (Jurnal Hasil Pengabdian kepada Masyarakat Universitas Jember, 2024)
Education is essential for every individual, as everyone has the right to grow through learning. Education is fostered by promoting a culture of reading, writing, and numeracy for all members of society. Despite achieving a 99.1% literacy rate, Indonesia still struggles with a low reading culture. It appears that literacy skills do not necessarily correlate with people's interest in reading. To address this, a literacy program aimed at boosting students' reading interest through the development of a digital library was implemented at MTs Bustanul Ulum in Locare Village. The KKN Back To Village III program, which took place from August 11 to September 9, 2021, focused on the theme of "Returning to Home." During the four-week program, it was discovered that the principal and teachers of MTs Bustanul Ulum desired to have library facilities at the school. Although some students showed an interest in reading, this was hindered by their lack of motivation, preventing an increase in reading interest. As a result of the program, MTs Bustanul Ulum now has library facilities to support teaching and learning activities. However, the program did not have a significant impact on the students' reading interest, suggesting that future programs should place more emphasis on fostering students' enthusiasm for reading.